1988
DOI: 10.1002/cne.902780306
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain connections of the gustatory system in ictalurid catfishes

Abstract: Horseradish peroxidase tracing and extracellular electrophysiological recording techniques were employed to delineate prosencephalic connections of the gustatory system in ictalurid catfishes. The isthmic secondary gustatory nucleus projects rostrally to several areas of the ventral diencephalon including the nucleus lobobulbaris and the nucleus lateralis thalami. Injections of HRP in the vicinity of the nucleus lobobulbaris reveal an ascending projection to the telencephalon terminating in the area dorsalis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 57 publications
7
100
1
1
Order By: Relevance
“…Inputs from the SGN to this nucleus have also been reported in percomorphs [sunfish : Wullimann, 1988;tilapia: Yoshimoto et al, 1998] and in ostariophysans [crucian carp: Morita et al, 1980Morita et al, , 1983catfish: Kanwal et al, 1988;Lamb and Caprio, 1993]. In agreement with the present results, it has been reported that the pTGN of tilapia [Yoshimoto et al, 1998] and nucleus lobobulbaris in ictalurid catfishes, which is a possible homologous nucleus to the percomorph pTGN [Kanwal et al, 1988], project to the NDLI. DiI injections into the NDLI plus nucleus centralis in goldfish showed labeled neurons in the SGN and pTGN [Rink and Wullimann, 1998].…”
Section: Nucleus Diffusus Lobi Inferiorissupporting
confidence: 82%
See 1 more Smart Citation
“…Inputs from the SGN to this nucleus have also been reported in percomorphs [sunfish : Wullimann, 1988;tilapia: Yoshimoto et al, 1998] and in ostariophysans [crucian carp: Morita et al, 1980Morita et al, , 1983catfish: Kanwal et al, 1988;Lamb and Caprio, 1993]. In agreement with the present results, it has been reported that the pTGN of tilapia [Yoshimoto et al, 1998] and nucleus lobobulbaris in ictalurid catfishes, which is a possible homologous nucleus to the percomorph pTGN [Kanwal et al, 1988], project to the NDLI. DiI injections into the NDLI plus nucleus centralis in goldfish showed labeled neurons in the SGN and pTGN [Rink and Wullimann, 1998].…”
Section: Nucleus Diffusus Lobi Inferiorissupporting
confidence: 82%
“…Involvement of this area in the control of feeding and aggressive behavior has been suggested by electrical stimulation experiments in cichlids [Demski and Knigge, 1971;Demski, 1973]. Gustatory inputs to this structure have been reported in acanthopterygian teleosts [sunfish : Wullimann, 1988;tilapia: Yoshimoto et al, 1998] and in ostariophysan teleosts [catfish: Kanwal et al, 1988;Lamb and Caprio, 1993;Lamb and Finger, 1996; crucian carp: Morita et al, 1980Morita et al, , 1983 for review see Meek and Nieuwenhuys, 1998]. In an acanthopterygian teleost Thamnaconus, visual inputs via the corpus glomerulosum (CG) to the inferior lobe have also been reported [Sakamoto and Ito, 1982].…”
Section: Introductionmentioning
confidence: 97%
“…HRP injections were accomplished by an insect pin coated with a paste of HRP (Finger, 1976) or delivered centrally using iontophoresis (Kanwal et al, 1988). For small iontophoretic injections of HRP in the reticular formation, a train of positive current pulses of 3-5 A (duration of pulse and interstimulus interval: 5 or 10 sec) was applied for 10 -15 min using a A360, WPI constant current stimulator.…”
Section: Methodsmentioning
confidence: 99%
“…Octavolateral as well as somatosensory information reaches the Dm, Dc and Dl mediated by the ventromedial thalamic nucleus (Ito et al 1986) and the preglomerular complex (Murakami et al 1986a,b;Striedter 1991;Yamamoto & Ito 2005a,b, 2008Northcutt 2006). Gustatory information reaches mainly the Dm relayed by a portion of the preglomerular complex or its homologue (Kanwal et al 1988;Yoshimoto et al 1998), reaching a region presumably distinct from octavolateral terminal zones within the Dm (Yamamoto & Ito 2005b). Ascending pathways mediated by the preglomerular complex enumerated above exhibit a considerable degree of modality-specific organization Yamamoto & Ito 2008), similarly to mammalian thalamo-cortical pathways.…”
Section: Sensory Pathways To the Telencephalonmentioning
confidence: 99%